2016
DOI: 10.1167/iovs.16-19514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraocular Lens Opacification on Light Scatter, Stray Light, and Overall Optical Quality/Performance

Abstract: Citation: Werner L, Stover JC, Schwiegerling J, Das KK. Effects of intraocular lens opacification on light scatter, stray light, and overall optical quality/ performance. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
(72 reference statements)
1
29
1
Order By: Relevance
“…7 In two other studies, on a distinct opacification pattern, a steep decline of MTF values was demonstrated. 20,30 In the current study, not all analyzed lenses demonstrated significant MTF effects. The SR of two IOLs (case 1 and 4) was lower than that of the control lens only by 4% at the 3-mm pupil.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…7 In two other studies, on a distinct opacification pattern, a steep decline of MTF values was demonstrated. 20,30 In the current study, not all analyzed lenses demonstrated significant MTF effects. The SR of two IOLs (case 1 and 4) was lower than that of the control lens only by 4% at the 3-mm pupil.…”
Section: Discussioncontrasting
confidence: 52%
“…Two studies reported light scattering from lens explants, however, the etiology of the calcification process of those lenses differ from that of the IOLs included in the current study. 20,28 Werner at al. 20 studied extended to the haptics in some cases: one silicone lens with dense central opacification that was explanted from a patient with asteroid hyalosis, and four PMMA lenses had snow-flake degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Straylight from larger particles (e.g. glistenings, surface deposits) has been studied [3][4][5][6]. Submicron particles have also been found in IOLs (i.e.…”
Section: Introductionmentioning
confidence: 99%